Effects of inertia correction and resistive load on fatigue during repeated sprints on a friction-loaded cycle ergometer - Bogdanis, G.; Papaspyrou, A.; Lakomy, H.; Nevill, M. (Journal of Sports Sciences, 2008)
Seven 6 s sprints with 30 s recovery between sprints were performed against two resistive loads: 50 (L50) and 100 (L100) g · kg-1 body mass. Inertia-corrected and -uncorrected peak and mean power output were calculated. Corrected peak power output in corresponding sprints and the drop in peak power output relative to sprint 1 were not different in the two conditions, despite the fact that mean power output was 15-20% higher in L100 (P < 0.01). The effect of inertia correction on power output was more pronounced for the lighter load (L50), with uncorrected peak power output in sprint 1 being 42% lower than the corresponding corrected peak power output, while this was only 16% in L100. Fatigue assessed by the drop in uncorrected peak and mean power output in sprint 7 relative to sprint 1 was less compared with that obtained by corrected power values, especially in L50 (drop in uncorrected vs. corrected peak power output: 13.3 ± 2.2% vs. 23.1 ± 4.1%, P < 0.01). However, in L100, the difference between the drop in corrected and uncorrected mean power output in sprint 7 was much smaller (24.2 ± 3.1% and 21.2 ± 2.7%, P < 0.01), indicating that fatigue may be safely assessed even without inertia correction when a heavy load is used. In conclusion, when inertia correction is performed, fatigue during repeated sprints is unaffected by resistive load. When inertia correction is omitted, both power output and the fatigue profile are underestimated by an amount dependent on resistive load. In cases where inertia correction is not possible during a repeated sprints test, a heavy load may be preferable.